2013
DOI: 10.1038/ismej.2013.104
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil bacterial and fungal communities to extreme desiccation and rewetting

Abstract: The microbial response to summer desiccation reflects adaptation strategies, setting the stage for a large rainfall-induced soil CO 2 pulse upon rewetting, an important component of the ecosystem carbon budget. In three California annual grasslands, the present (DNA-based) and potentially active (RNA-based) soil bacterial and fungal communities were tracked over a summer season and in response to controlled rewetting of intact soil cores. Phylogenetic marker genes for bacterial (16S) and fungal (28S) RNA and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

83
527
12
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 753 publications
(653 citation statements)
references
References 60 publications
(67 reference statements)
83
527
12
3
Order By: Relevance
“…In contrast with bacteria, the potentially active soil fungal community showed little response to differing precipitation treatments and to subsequent wet-up. This is consistent with the expected larger resistance of fungi than bacteria to drought (Bapiri et al, 2010;Barnard et al, 2013) and the generally more stable properties of fungal food webs compared to bacterial food webs (de Vries et al, 2012a).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast with bacteria, the potentially active soil fungal community showed little response to differing precipitation treatments and to subsequent wet-up. This is consistent with the expected larger resistance of fungi than bacteria to drought (Bapiri et al, 2010;Barnard et al, 2013) and the generally more stable properties of fungal food webs compared to bacterial food webs (de Vries et al, 2012a).…”
Section: Discussionsupporting
confidence: 84%
“…Although there has been substantial interest in identifying the C sources consumed upon rewetting (Miller et al, 2005;Xiang et al, 2008;Boot, 2011;Parker and Schimel, 2011;Kakumanu et al, 2013), that question is to a large degree distinct from that of understanding the physiological state of the soil community before and during the wet-up process. From the microbial activity point of view, microbial communities indigenous to California annual grasslands have been shown to react extremely rapidly to rewetting Placella et al, 2012;Barnard et al, 2013). In a recent study, we found that different bacterial phyla responded differently to rewetting in California grasslands, displaying contrasting life strategies , resulting from long-term evolutionary adaptation.…”
Section: Introductionmentioning
confidence: 84%
“…In contrast, Weber et al (2013) reported a positive response of Ascomycetes to nitrogen addition, whereas many of the abundant Ascomycete OTUs decreased in relative abundance in our nitrogen treatment. Also, in contrast to prior studies, added nitrogen or drought did not increase the relative abundance of Actinobacteria (Ramirez et al, 2012;Barnard et al, 2013). Further work is needed to understand whether these taxonomic groups are not consistent in their responses (Philippot et al, 2010), or whether such responses depend on the community and system context.…”
Section: Discussioncontrasting
confidence: 57%
“…Broadly speaking, the taxonomic composition observed in this study is similar to that found in other terrestrial litter and soil systems. The majority of fungal sequences in this study were Ascomycota and Basidiomycota (Barnard et al, 2013;Voriskova and Baldrian, 2013;Weber et al, 2013), and Proteobacteria, Bacteriodetes and Actinobacteria made up most of the bacterial diversity (Castro et al, 2010;Sheik et al, 2011;Barnard et al, 2013;Kim et al, 2014). In contrast, many soils contain a large fraction of Acidobacteria (Castro et al, 2010;Sheik et al, 2011;Barnard et al, 2013;Kim et al, 2014), but they represented o1% of our litter communities.…”
Section: Discussionmentioning
confidence: 69%
“…PCR products were purified, pooled and sequenced on a 454 GS FLX Titanium sequencer (Roche 454 Life Sciences, Branford, CT, USA). Detailed methodology, downstream processing and bioinformatics analysis were described previously by Singh et al (2014) and Barnard et al (2013). Operational taxonomic unit tables used to determine the microbial abundances were rarefied to 733 and 784 sequences for bacteria and fungi, respectively, to ensure even sampling depth.…”
Section: Molecular Analysismentioning
confidence: 99%